Identification of Ros Produced by Photodynamic Activity of Chlorophyll/Cyclodextrin Inclusion Complexes. (16th October 2012) - Cellamare, Barbara M.; Fini, Paola; Agostiano, Angela; Sortino, Salvatore; Cosma, Pinalysa
Abstract Photodynamic therapy (PDT) is a way of treating malignant tumors and hyperproliferative diseases. It is based on the use of photosensitizer, herein the chlorophyll a (chl a), and a light of an appropriate wavelength. The interaction of the photosensitizer (PS) with the light produces reactive oxygen species (ROS), powerful oxidizing agents, which cause critical damage to the tissue. To solubilize chl a in aqueous solution and to obtain it as monomer, we have used cyclodextrins, carriers which are able to interact with the pigment and form the inclusion complex. The aim of this study is to examine which types of ROS are formed by Chl a/cyclodextrin complexes in phosphate buffered solution and cell culture medium, using specific molecules, called primary acceptors, which react selectively with the reactive species. In fact the changes of the absorption and the emission spectra of these molecules after the illumination of the PS provide information on the specific ROS formation. The 1O2 formation has been tested using chemical methods based on the use of Uric Acid (UA), 9, 10‐diphenilanthracene (DPA) and Singlet oxygen sensor green (SOSG) and by direct detection of Singlet Oxygen (1O2) luminescence decay at 1270 nm. Moreover, 2, 7‐dichlorofluorescin and ferricytochrome c (Cyt Fe3+) have been used to detect the formation of hydrogen peroxide and superoxide radical anion, which reduces Fe3+ of the ferricytochrome to Fe2+, respectively.